Clinical Repeatability and Inter-Method Agreement of VITA Easyshade Advance 4.0 and Rayplicker Cobra for Tooth Shade Determination: An Exploratory Cross-Sectional Study - L. Portero-Ruz; M. Valor-Priego; A. Martín-Vacas; M. M. Paz-Cortés; J. Mena-Álvarez; C. Rico-Romano (Diagnostics, 2026)
Background: Instrumental shade determination may reduce some sources of subjectivity associated with visual shade selection, but device repeatability and interchangeability remain clinically relevant concerns. Objective: The aim of this study was to evaluate the reproducibility and clinical utility of two spectrophotometric devices (Easyshade and Rayplicker Cobra) for tooth shade measurement and selection. Methods: In total, 35 adults were evaluated at seven predefined maxillary tooth regions: the cervical, middle, and incisal thirds of teeth 2.1 and 2.3, and the middle third of tooth 2.6. Each instrumental measurement was repeated three times, with complete removal and repositioning of the device between readings. Visual shade selection using the VITA Classical guide was performed once per site by the same trained operator, whose normal colour vision had been confirmed before data collection. Teeth were kept hydrated, patients remained in the same position, and both devices were calibrated according to the manufacturers’ instructions. Intra-device strict repeatability and inter-method agreement were assessed descriptively and using Cohen’s Kappa, as appropriate. Results: Descriptive pooled strict repeatability was 52.2% for Easyshade and 53.1% for Rayplicker Cobra. Repeatability varied by tooth and region. Inter-device agreement was predominantly slight to fair (0.053–0.386). Easyshade showed moderate-to-substantial agreement with the visual comparator in selected regions, with the highest Kappa in the middle third of tooth 2.1 (0.619), whereas Rayplicker Cobra did not exceed fair agreement (maximum 0.362). Conclusions: Both spectrophotometers showed similar descriptive strict repeatability percentages; however, their low inter-device agreement indicates that their categorical shade outputs should not be considered interchangeable. The greater agreement of Easyshade with VITA Classical in selected regions reflects inter-method comparability rather than superior trueness, as no independent instrumental reference standard was used.